Fabrication of (1-x)Ba(Zr0.2Ti0.8)O3-x(Ba0.7Ca0.3)TiO3 ceramics saving energy by molten-salt synthetic method. (2018) - Mathrmool, Krailas; Kumar, Nitish; Sumang, Rattiphorn
Abstract: Lead-free (1- x )Ba(Zr0.2 Ti0.8 )O3 – x (Ba0.7 Ca0.3 )TiO3 ; BZT-BCT ceramics with x BCT=0-0.70 mol% were successfully prepared by the molten-salt method using NaCl and KCl as the flux. The samples were calcined and sintered between 700-1200 °C and 1000-1300 °C for 3 h. The results indicated that the synthesis temperature of BZT-BCT was about 350°C lower than that reported by solid-state reaction methods. The effect of x BCT content on phase formation, microstructure and dielectric properties were also studied. The phase of the samples showed pure perovskite structure for all conditions. The results indicated that a phase transformation from rhombohedral to tetragonal structure occurs in the system, with increase in x BCT content. The microstructure was studied by Scanning Electron Microscope. The addition of x BCT contents could suppress the grain growth which showed the average grain size dramatically decreased from 412 to 259 nm. The density values of the samples were increased and were maximum at x BCT=0.50 (5.6 g/cm 3 ) and then dropped with increased of x BCT contents. The maximum piezoelectric constant (∼250 pC/N) and dielectric constant at T room ( ε r =2, 023) was found in the composition of 0.70BZT-0.30BCT.